The Prognostic Impact of High On-Treatment Platelet Reactivity with Aspirin or ADP Receptor Antagonists: Systematic Review and Meta-Analysis. (13th October 2014) - D'Ascenzo, Fabrizio; Barbero, Umberto; Bisi, Marta; Moretti, Claudio; Omedè, Pierluigi; Cerrato, Enrico; Quadri, Giorgio; Conrotto, Federico; Zoccai, Giuseppe Biondi; DiNicolantonio, James J.; Gasparini, Mauro; Bangalore, Sripal; et al.
Abstract : Objective . Negative results of recent randomized clinical trials testing the hypothesis of target therapy for patients with high on-treatment platelet reactivity (HOPR) have questioned its independent impact on clinical outcomes. 26 studies with 28.178 patients were included, with a median age of 66.8 (64–68) and 22.7% (22.4–27.8), of female gender. After a median follow-up of 1 year (0.1–1), cardiac adverse events occurred in 8.3% (3–11; all results are reported as median and interquartile range) of patients. Pooling all studies together, on-treatment platelet reactivity significantly increased the risk of adverse events (OR 1.33 [1.09, 1.64], I 2 = 0 % ). However, a sensitivity analysis showed that HOPR did not increase the risk of adverse events for patients with ACS, AMI, or stable angina as well as patients resistant to aspirin, ADP antagonists, or both. For all studies, publication bias was formally evident; after adjusting for this, HOPR did not significantly increase adverse cardiac events (OR 1.1 : 0.89–1.22, I 2 0%). Conclusions . After adjusting for clinical confounders (like risk factors and clinical presentation) and for relevant publication bias, HOPR was not an independent prognostic indicator in unselected patients with both stable and unstable coronary disease for an adverse cardiac event. The clinical importance of HOPR for high-risk populations remains to be assessed.